To simplify the expression \( 3^7 \cdot 3^{-9} \) using the properties of integer exponents, we can use the rule that states \( a^m \cdot a^n = a^{m+n} \).
-
Combine the exponents: \[ 3^7 \cdot 3^{-9} = 3^{7 + (-9)} = 3^{-2} \]
-
To express this with only positive exponents, recall that \( a^{-n} = \frac{1}{a^n} \): \[ 3^{-2} = \frac{1}{3^2} \]
-
Now, simplify \( 3^2 \): \[ \frac{1}{3^2} = \frac{1}{9} \]
Thus, the expression \( 3^7 \cdot 3^{-9} \) simplifies to: \[ \frac{1}{9} \]
The final answer without remaining exponents is: \[ \frac{1}{9} \]